IP(3) receptors: take four IP(3) to open - Taylor, Colin W (Sci Signal, 2016)
Inositol 1,4,5-trisphosphate receptors (IP(3)R) and ryanodine receptors are the channels responsible for Ca(2+) release from the endoplasmic and sarcoplasmic reticulum. High-resolution structures of these enormous channels are beginning to reveal the inter-domain re-arrangements that link binding of their key regulators (IP(3) and/or Ca(2+)) to opening of the Ca(2+)-permeable pore. Activation of IP(3)R is initiated when IP(3) causes its clam-like binding domain to close, thereby disrupting interactions with other domains that may then communicate with the pore. All four IP(3)-binding sites within the tetrameric IP(3)R must bind IP(3) before the channel can open. This has important consequences for the distribution of both IP(3) and IP(3)R activity within cells, and it may contribute to the complex spatial organization of intracellular Ca(2+) signals.